Overhead Vision System for Mobile Robot Orientation Detection - Fadzilah binti Hashim (School of Computer & Communication Engineering, 2010)
Robot cooperation and coordination is absolutely necessary in many industrial applications. The computation of a mobile robot position and orientation is a common task in the area of computing vision and image processing. For a successful application, it is important that the position and orientation of the mobile robot are properly determined. Computing the orientation is not a straightforward technique. Number of methods has already been studied by many researchers. These methods include the concepts of geometric moments, complex moments, and principal component analysis. In this work, a simple procedure for determining the orientation of the mobile robot using overhead vision system is presented and analysed.